The Impact of Migration Processes on Crime Rates O Impacto dos Processos de Migração nas Taxas de Criminalidade - Prodan, Tetyana (Revista Jurídica Portucalense, 2024)
The aim of the study is to assess the impact of migration indicators on the crime rates in selected countries. The research employed cluster, correlation and regression analyses as the main methods. The analysis established that the impact of migration on crime in different countries differs significantly in terms of strength and direction. In particular, it was found that the increased share of refugees in the population of Egypt, Mauritius and the USA is associated with the decreased Crime Index. The obtained results indicate that the degree and direction of the influence of migration on crime depends on the specific situation in the country, which covers various aspects of social, political, economic and other dimensions. The conclusions of the research can be useful for shaping migration policy and preventing bias in this process.
Keywords: кримінологія; транснаціональна злочинність; злочинність